Enkapsulan ekstrak liang teh hasil seduhan pada berbagai pH sistem sebagai bahan inti: karakteristik fisikokimia [Physicochemical Characteristic of liang tea extract encapsulation on various pH] - Sherlirianti Sherlirianti; Yohana Sutiknyawati Kusuma Dewi; Dzul Fadly (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2023)
Liang tea is a traditional drink made from herbal ingredients and tea ingredients which are functional as antioxidants. The use of a cup of tea leaves produces an interesting red-purple color, partly because it contains brazilin pigment. The color of the liang infusion is affected by pH but it is not yet known whether it has an effect on its physicochemical characteristics. The obstacle faced is because the form of the drink in the form of steeping becomes impractical so it needs modification, one of which is in the form of an encapsulant. One of the conditions for the steeping pH is achieved by using citrate buffer. Our study aimed to obtain the steeping pH conditions that produce liang tea extract as the core ingredient to obtain the best encapsulant based on physicochemical characteristics. The research design used complete randomization with 4 treatment levels, namely the addition of citrate buffer to pH 4.25; 5.07; 6.06 and without administration of citrate buffer (pH 6.37). The physicochemical characteristics of the encapsulant were observed for pH, water content, solubility, polyphenol content and antioxidant activity in liang tea extract as the core and encapsulant material. The results showed that liang tea extract brewed at system pH 4.25 had antioxidant activity (70.48 ± 0.81 %), produced encapsulants with highest total polyphenols (493.75 ± 12.50 mg GAE/g encapsulant) and antioxidant activity (72.24 ± 3.56 %) but also highest water content (10.76 ± 0.08 %) while the highest solubility was obtained in the encapsulant with the main ingredient of liang tea extract which was brewed at a system pH of 6.37.